Time-Dependent Simulation Identifies Critical Hour Phase of Intestinal Acute Injury in Sepsis Mouse Model - Istanti, Yusrina; Anggoro, Naufal Sebastian; Husain, Sofian Azalia; Azzahara, Salma Yasmine (International Journal of Cell and Biomedical Science, 2024)
Background: Understanding the dynamic process of intestinal injury and repair during sepsis is essential for identifying optimal therapeutic windows. This study aimed to determine the critical time phase of intestinal acute injury by analyzing histological changes over a 24-hour period in a sepsis mouse model. Methods: Mice were divided into four groups—Control, 9 h, 12 h, and 24 h—and intestinal tissue samples were assessed using the Chiu histological scoring system. A time-dependent simulation was conducted to evaluate average changes in tissue damage and to identify key transition points between injury and recovery phases. Statistical analysis was performed using one-way ANOVA followed by post hoc comparisons to determine significant differences among time points. Results: The simulation demonstrated a marked increase in intestinal damage between 9 h and 12 h, followed by partial recovery at 24 h. Statistical analysis revealed a significant difference (p < 0.05) corresponding to this shift. These findings suggest that peak tissue injury occurs around 12 hours post-sepsis induction, preceding the onset of repair mechanisms. Conclusion: The study provides quantitative insight into the temporal progression of intestinal injury in sepsis, identifying the 12–24 hour period as a critical therapeutic window for potential interventions.